Effect of peak sun hour on energy productivity of solar photovoltaic power system - Prisma Megantoro; Muhammad Akbar Syahbani; Irfan Helmi Sukmawan; Sigit Dani Perkasa; Pandi Vigneshwaran (Institute of Advanced Engineering and Science, 2022)
A solar cell is a type of renewable energy engineering technology that can convert photons coming from the sun to be converted into electrical energy. The amount of energy that can be converted by a solar cell is determined by the effective insolation time. Peak sun hours (PSH) are the focus of this research. This PSH analysis aims to determine the potential for solar energy obtained in geographical locations throughout the year. Geographical location and the position of the astronomical coordinates of a certain area affect PSH. Therefore, the orientation of solar panel installation, including the height, slope, and latitude of the solar panel surface needs to be considered in order to get maximum solar energy. The results of this study can be used by technicians in determining the orientation of solar panel development in an area.